2012
DOI: 10.1242/jcs.114488
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the multi-copy mouse Y gene Sly causes sperm DNA damage and abnormal chromatin packaging

Abstract: SummaryIn mouse and man Y chromosome deletions are frequently associated with spermatogenic defects. Mice with extensive deletions of nonpairing Y chromosome long arm (NPYq) are infertile and produce sperm with grossly misshapen heads, abnormal chromatin packaging and DNA damage. The NPYq-encoded multi-copy gene Sly controls the expression of sex chromosome genes after meiosis and Sly deficiency results in a remarkable upregulation of sex chromosome genes. Sly deficiency has been shown to be the underlying cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…With the exception of the male sex-determining gene, Sry , surviving ancestral Y-linked single-copy genes are broadly expressed, both in the adult and throughout development (Bellott, et al 2014). In contrast, ampliconic/multi-copy genes on the sex chromosomes tend to be expressed specifically in male germ cells, with potential roles in postmeiotic spermatids (Cocquet, et al 2010, Comptour, et al 2014, Mueller, et al 2008, Mueller, et al 2013, Reynard, et al 2009, Riel, et al 2013, Sin, et al 2012b). In this section, we provide examples of single-copy and ampliconic/multi-copy genes from mouse genetic studies in the regulation of spermatogenesis.…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Genmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of the male sex-determining gene, Sry , surviving ancestral Y-linked single-copy genes are broadly expressed, both in the adult and throughout development (Bellott, et al 2014). In contrast, ampliconic/multi-copy genes on the sex chromosomes tend to be expressed specifically in male germ cells, with potential roles in postmeiotic spermatids (Cocquet, et al 2010, Comptour, et al 2014, Mueller, et al 2008, Mueller, et al 2013, Reynard, et al 2009, Riel, et al 2013, Sin, et al 2012b). In this section, we provide examples of single-copy and ampliconic/multi-copy genes from mouse genetic studies in the regulation of spermatogenesis.…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Genmentioning
confidence: 99%
“…Its long arm contains the highly amplified germ cell-specific gene families Sly , Srsy , and Ssty , all of which were acquired during the evolution of the rodent lineage (Soh, et al 2014). Mice lacking part or all of the long-arm genes show mild-to-severe defects in sperm morphology, fertilization, and fertility (Burgoyne, et al 1992, Conway, et al 1994, Riel, et al 2013, Suh, et al 1989, Toure, et al 2004b). On the short arm, Eif2s3y is the sole factor essential for spermatogonial proliferation (Mazeyrat, et al 2001).…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Genmentioning
confidence: 99%
See 1 more Smart Citation
“…As yet, the root cause of the skewing remains unknown. However, it is known to be regulated by a conflict between the sex-linked ampliconic transcriptional regulators Slx and Sly in haploid spermatids [8][9][10][11][12]. The prevailing model is that one or more X-linked genes acts post-meiotically to favour the production of female offspring, and that these genes in turn are repressed by (Y-linked) Sly and activated by (X-linked) Slx.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, males without the MSYq region exhibit more severe sperm defects than Sly-deficient males, associated with a higher de-repression of XY genes and loss of additional epigenetic marks [24][25][26][27]. This difference may be due to insufficient knockdown of Sly, but we have observed that limited SLY protein remains in Sly-deficient males [25] (J.C. MAW, unpublished data); it is therefore more likely that another MSYq gene contributes to the regulation of post-meiotic sex chromosome gene expression.…”
Section: Introductionmentioning
confidence: 99%